2019
DOI: 10.2340/16501977-2528
|View full text |Cite
|
Sign up to set email alerts
|

Spastic co-contraction, rather that spasticity, is associated with impaired active function in adults with acquired brain injury: A pilot study

Abstract: LAY ABSTRACTSpasticity and spastic co-contraction are expressions of muscle overactivity that occur in spastic paresis syndrome after a brain injury. The objective of the present pilot study was to improve our understanding of the respective adverse consequences of spasticity and spastic co-contraction on motor disability. In contrary to spasticity, spastic co-contraction is strongly associated with motor impairment in subjects with brain injury. Therapies should be directed toward reducing spastic co-contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Increased muscle co-contraction leads to impairment in the upper limb motor function in stroke survivors. Previous studies reported that increased muscle co-contraction had a negative effect on voluntary movement ( Chae et al, 2002 ; Chalard et al, 2019 ). It could bring about increased duration of the movement, muscle discoordination, and decreased range of movement ( Arene and Hidler, 2009 ; Gross et al, 2015 ; Sarcher et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased muscle co-contraction leads to impairment in the upper limb motor function in stroke survivors. Previous studies reported that increased muscle co-contraction had a negative effect on voluntary movement ( Chae et al, 2002 ; Chalard et al, 2019 ). It could bring about increased duration of the movement, muscle discoordination, and decreased range of movement ( Arene and Hidler, 2009 ; Gross et al, 2015 ; Sarcher et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that this premature activation reflects a compensatory phenomenon allowing the body weight to be absorbed in foot strike ( 21 , 22 ). No relation was found between an improvement in ADF post-MNB and TS spasticity either, highlighting that spasticity assessment does not predict what happens during movement ( 4 , 38 ).…”
Section: Discussionmentioning
confidence: 82%
“…During an early swing, the TA muscle contracts concentrically, allowing the ankle to perform a rapid dorsiflexion movement, bringing the ankle to 0° for foot clearance ( 2 , 37 ). Overactivity of the calf muscles, especially the triceps surae, during this period corresponds to spastic co-contraction ( 4 ) involved in limiting active movement ( 38 ) by reversing dorsiflexor torque to plantar-flexor torque ( 39 ). This observation, described as a “stretch-sensitive paresis” ( 4 ), was noted for 26% of the cases in a hemiplegic population of 18 subjects ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…root mean square value during maximal isometric voluntary elbow flexion contraction (Chalard et al, 2019). This maximal voluntary contraction was obtained from a series of three fivesecond voluntary maximal contractions, two minutes apart, performed on an isokinetic ergometer with shoulder flexion of 80 • , an internal rotation of 90 • and the bust attached.…”
Section: Data Processingmentioning
confidence: 99%
“…These observations are in agreement with the general consensus on impaired muscle co-activation after stroke, which in part involves the alteration of co-contraction in this population ( Roh et al, 2013 ). Co-contraction is related to an involuntary contraction of both synergistic agonist and antagonist muscles ( Gracies, 2005 ) that occurs in healthy subjects but which is excessive in stroke subjects ( Angel, 1975 ) and can be partly responsible for the alteration of the motor function of the upper paretic limb ( Chollet et al, 1991 ; Crafton et al, 2003 ; Ohn et al, 2013 ; Chalard et al, 2019 ). It should be noted that in this study, the synergistic muscles are all muscles involved in a movement.…”
Section: Introductionmentioning
confidence: 99%